Synthesis and Physico-Chemical Characterization of Vanadium Phosphorus Oxide Catalyst for Selective Oxidation of N-Butane to Maleic Anhydride - Mat Hussin, Ahmad Raslan (2006)
Vanadium phosphorus oxide (VPO) catalyst is famously known to catalyze the selective oxidation of n-butane to maleic anhydride. In this study, VPO catalysts were synthesized using different sources of phosphorus i.e. H3PO4 and H4P2O7. VPO catalysts obtained from VOHPO4·0.5H2O precursor were prepared by using VPD method (dihydrate route). This resulting precursor, VOHPO4·0.5H2O was calcined at 673 K in a flow reaction of n-butane/air mixture (0.75 % n-butane in air) for 36 and 75 h to give the final catalysts denoted as VPDortho35, VPDortho75 (using H3PO4) and VPDpyro36,VPDpyro75 (using H4P2O7). Three main peaks appeared at 2θ = 23.0o, 28.5o and 29.9o in PXRD diffractogram was assigned to the presence of the vanadyl pyrophosphate phase, (VO)2P2O7. The results show that VPO catalysts derived from H3PO4 and H4P2O7 displayed a quite similar P/V ratio value although they were prepared using different phosphorus sources and duration. However, H3PO4-based catalysts gave a higher average vanadium valence as compared to the H4P2O7-based catalysts. It was found that using H4P2O7 as a phosphorus source, decreasing of the average number from 4.26 to 4.18 and 4.36 to 4.27 i.e. a reduction of V5+ oxidation state from 26 to 18 % and 36 to 27 %, respectively. Prolonged calcination also reduced the average oxidation number for both catalysts and this evidence showed that longer calcination favours V4+ formation and resulted in a lower of V5+ percentage. The surface area is another major factors that controlling the catalysts activities. The replacement of H3PO4 with H4P2O7 has resulted in higher surface area and increasing the duration (36 to 75 h) also led to the increasing in the surface area. The SEM micrograph showed that, the principle surface morphology of the catalyst is the same i.e. arranged into the characteristic rosette-shaped clusters. The nature and behaviour of the oxidants available in the catalyst were studied by means of this combination transient of kinetic techniques i.e. O2 temperature programmed desorption (TPD), temperature programmed reduction (TPR) in H2 and temperature programmed oxidation (TPO) in O2. The anaerobic temperature programmed reaction (TPRn) of n-butane over both catalysts produced selective products i.e. but-1-ene, but-1,3-diene and furan. Two interesting points can be noted here. First, TPRn profiles showed that VPDpyro75 gave higher selectivity towards production of butene and butadiene and lower percentage amount of unselective products (CO and CO2) compared to that of VPDortho75. Secondly, the most interesting of this reaction is that furan was observed at 840 and 1050 K for both catalysts (VPDortho75 and VPDpyro75). Furan was not found in a previous study using butane feed over (VO)2P2O7 prepared by ‘classical’ organic method. This is in an agreement with the fact that dihydrate method (VPD method) prepared VPO catalyst is more active and selective than the organic method. Since butene, butadiene and furan were found to be one of the selective products, this suggested that the mechanism of the oxidation of n-butane to maleic anhydride is sequential.